Influence of Type 2 Diabetes mellitus on periodontal conditions in a population of Dhaka City - Ahmed, Salauddin; Khan, Md Asif Iqbal; Iqbal, Md Ashif; Hossain, Mahfuz; Ahmed, Shahabuddin; Ahmed, Suraiya (Update Dental College Journal, 2016)
Background: Periodontal disease is a destructive type of oro-dental disease because of potential damage to the dentition resulting early loss of teeth. Patients suffering from both diabetes mellitus and periodontal disease present the challenge of managing two chronic diseases as each of which may influence the other. Purpose: The aim of this study was to find out the influence of periodontal disease in patients with type 2 diabetes mellitus in a population of Dhaka City. Methods: The clinical study carried out in a reputed dental clinic of Dhaka, Uttara; consist of 132 type 2 diabetic patients as cases and 30 non-diabetic persons as controls. The cases include two age groups: one of which was considered as middle age group (4055yrs, both male and female) while the other age group consisting participants both sexes of 56-70yrs, were considered as elderly group. The middle age group was again divided into two categories, group A consisting of 22 patients on non-drug therapy but on regular physical exercise, restricted diet and other directions as per physician, while patients from group B were on oral drug therapy (oral hypoglycemic tablets). Thirty (30) non-diabetic persons belonging to both sexes and aged between 4055yrs (n=15) and 5670 yrs (n=15) respectively were selected as controls. Clinical exam was performed by a trained periodontologist and Plaque Index (PI) and Gingival Index (GI) were determined according to the preset criteria. The periodontal pocket depth (PPD), Clinical attachment loss (CAL)) and severity of periodontitis (mild, moderate, severe) were recorded among the two groups of NIDDM cases and the healthy controls. Results: An increase in the periodontal destruction (CAL) was apparent in type 2 diabetic patients compared to the non-diabetic controls. Drug dependent middle age group (both male-female) demonstrated more disease prevalence than the same age group of non-drug dependent NIDDMs. All the elderly patients under oral drug therapies had high prevalence of periodontal disease of variable severity. Non-diabetic controls presented with 13.3% and 33.3% disease prevalence in 40-55 yrs and 56-70 yrs age groups respectively. Conclusion: Periodontal disease is more prevalent in patients with Type 2 diabetes mellitus and particularly patients on oral hypoglycemic agents had more periodontal tissue break down. It was also apparent from the findings of the study that periodontal destruction is more prevalent in ageing subjects suffering from NIDDM. Update Dent. Coll. j: 2016; 6 (1): 35-39